OPPORTUNITIES TO DEVELOP STUDENT THINKING THROUGH THE STUDY OF CHILDREN'S LITERATURE - Tileumuratova Gulnaz Tajibay kizi (American Journals, 2023)
In recent years, at a time when literature, art and culture, reading are given special importance in our country, the emergence of scientific research dedicated to the study of children's literature is of urgent importance. In this article, it can be observed that Karakalpak is similar to games and songs performed in Russian, Tatar, Kazakh, Turkmen, Tajik, Dagestani, Georgian, Latvian and other nations of the world. This study focuses on the myriad opportunities for fostering cognitive development and critical thinking skills in students through the exploration of children's literature. The study delves into the multifaceted ways in which exposure to diverse genres of literature tailored for young readers can serve as a catalyst for enhancing cognitive abilities and promoting analytical thinking. The article draws on various perspectives, encompassing cognitive development, critical thinking skills, creative thinking, and cultural literacy, providing a comprehensive overview of the cognitive benefits derived from engaging with children's literature.
Keywords: Children's literature, Tales, myths, legends, myths, exhortations, descriptions, short stories, narratives.